A RANDOMIZED, DOUBLE-BLIND, PLACEBO-CONTROLLED STUDY ON STANDARDIZED FENUGREEK SEED EXTRACT COMPOSITION FOR ENDURANCE ENHANCEMENT IN RECREATIONALLY ACTIVE YOUNG SUBJECTS - PRASAD ARVIND THAKURDESAI; PALLAVI ONKAR DESHPANDE; MADHURA MANDAR KARVE; DHANANJAY VASANT RAJE (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: To evaluate the efficacy and safety of 8-week supplementation with FEΔE (fenugreek seed extracts composition, standardized to 4-hydroxyisolecuine, trigonelline, and select glycosides) on endurance capacity in recreationally active young male subjects, in a randomized, double-blind, Placebo-controlled manner. Methods: The 153 male participants were randomized equally into three groups and received either 300 mg or 600 mg of FeΔE capsules or a matching Placebo. Each participant performed endurance exercise training four times per week and visited the study center on the day of recruitment (baseline) and end of week-4, and week-8. The efficacy outcome measures were endurance (overall, cardiovascular, respiratory, and metabolic), power, work, physical and central fatigue, and stress, whereas safety outcomes were adverse events monitoring, compliance, and biochemical laboratory measurements. Results: FEΔE supplementation (but not Placebo) showed statistically significant beneficial changes in overall (increased time to exhaustion and total distance run), respiratory (increased oxygen consumption), metabolic (increased metabolic equivalent and decreased non-esterified fatty acids levels), physical fatigue (decreased Wingate fatigue index), central fatigue (reduced visual analog score), and mental endurance (decreased mental domain score in the Multidimensional Fatigue Symptom Inventory-Short Form) during within the group (vs. baseline) comparisons. The safety outcome measures did not differ between the groups (FEΔE vs. Placebo). Conclusion: Eight weeks of FEΔE supplementation in recreationally active participants resulted in comprehensive endurance enhancement, including respiratory, metabolic, and mental endurance. FEΔE supplementation was found to be safe without serious adverse events.